2016
DOI: 10.24176/jkg.v2i1.549
|View full text |Cite
|
Sign up to set email alerts
|

Konseling Individual Dengan Teknik Modeling Simbolis Terhadap Peningkatan Kemampuan Kontrol Diri

Abstract: Penelitian dilakukan pada siswa yang memiliki kontrol diri rendah. Terdapat peserta didik yang terlibat pergaulan yang negatif di luar sekolah. Tujuan penelitian ini untuk mengembangkan kontrol diri penelitian menggunakan metode penelitian eksperimen kuasi dengan desain single subject dengan desain A-B. Penelitian pelaksanaan pengukuran baseline sebanyak tiga kali, intervensi konseling individu dengan teknik modeling simbolis dilaksanakan sebanyak empat sesi. Berdasarkan hasil uji percentage non-overlapping da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
6
0
5
Order By: Relevance
“…Research on the influence of counseling by Arumsari (2016), revealed that the application of effective counseling increased the self-control ability of grade 11 students in Vijaya Kusuma. Another study conducted by Saripah (2010) revealed that bullying victims experienced an increase in assertiveness and selfconfidence after receiving cognitive behavioral counseling.…”
Section: The Effect Of Counseling As a Methods Of Reconciliation On The Negative Psychological Effects Of Dating Violence Victimsmentioning
confidence: 99%
“…Research on the influence of counseling by Arumsari (2016), revealed that the application of effective counseling increased the self-control ability of grade 11 students in Vijaya Kusuma. Another study conducted by Saripah (2010) revealed that bullying victims experienced an increase in assertiveness and selfconfidence after receiving cognitive behavioral counseling.…”
Section: The Effect Of Counseling As a Methods Of Reconciliation On The Negative Psychological Effects Of Dating Violence Victimsmentioning
confidence: 99%
“…Group Counseling with Effective Modeling Techniques to Improve Self-Control Interventions provided using group counseling with modeling techniques have Vol.10, No.1, June 2021 proven effective for improving students' self-control. Research conducted by Arumsari (2016) said that modeling techniques proved effective in improving students' self-control abilities seen from improved scores of self-control abilities.…”
Section: B Grouping Variable: Kelasmentioning
confidence: 99%
“…Berdasarkan hasil penelitian Arumsari (2016) tentang konseling individual dengan teknik modeling simbolis terhadap peningkatan kemampuan kontrol diri diperoleh bahwa Konseling individu dengan teknik modeling simbolis efektif mengembangkan kontrol diri tiga siswa subjek penelitian pada semua sapek kontrol diri yaitu perasaan dan tingkah laku, disiplin, emosi dan nafsu. Penelitian juga dilakukan oleh Sari dkk (2017) tentang penerapan teknik modeling simbolis dalam meningkatkan perilaku tolerasi siswa kelas V SD Negeri 25 Banda Aceh diperoleh bahwa adanya peningkatan dan perubahan perilaku toleransi siswa kelas V SD Negeri 25 Banda Aceh setelah diberikan teknik modeling simbolis.…”
Section: Pendahuluanunclassified